Кооперація та інтеграція в аграрному бізнесі - Безус, Роман Миколайович; Bezus, Roman; Крючко, Леся Станіславівна; Kriuchko, Lesia (Дніпровський державний аграрно-економічний університет, 2020)
У статті висвітлено основні засади сутності кооперація та інтеграція в аграрному бізнесі. Досліджено, що кооперація як складна структурно-функціональна категорія розкривається певною системою елементів з чотирьох сторін: як форма організації праці; як інститут громадських відносин; як форма організації суспільного виробництва; як форма використання власності на засоби виробництва. Розглянуто процесно-складовий підхід, з точки зору якого сутність інтеграції як системи може бути визначена через властивості самоорганізації, адаптивності, раціонального використання ресурсів, ієрархічності, виділення провідної ланки, наявність єдиної мети для всіх складових, прагнення до рівноважного стану; як процесу через взаємодоповнення; розмежування відповідальності; цілеспрямоване регулювання; можливість застосування інновацій і досягнень науково-технічного прогресу, як організації характеризується властивостями корпоративності, координації факторів виробництва, раціональності, здатності до саморозвитку. Вивчено коопераційні та інтеграційні процеси, які можуть бути представлені як структурні перетворення взаємин суб'єктів аграрного бізнесу у разі вступу їх в коопераційну та інтеграційну взаємодію. Встановлено, що сучасний етап розвитку коопераційних і інтеграційних процесів характеризується зближенням принципів кооперації та інтеграції в умовах розвитку суспільного розподілу праці. The article describes the basic principles of cooperation and integration in the agrarian business. It has been investigated that cooperation as a complex structural and functional category is revealed by a certain system of elements from four parties: as a form of organization of labor — through a process that is applied at the same time, in the same place to produce the same product or group goods of one kind; as an institute of public relations — through cooperation of people, organizations, states in any kind of activity for achievement of common goals, realization of common interests; as a form of organization of social production — through stable ties of economic units, unite to jointly solve problems of economic nature; as a form of ownership of the means of production — through determining the interconnection and interdependence between the elements of the economic structure. The process-component approach is considered from the point of view of which the essence of integration as a system can be determined through the properties of self-organization, adaptability, rational use of resources, hierarchy, allocation of a leading link, presence of a common goal for all components, the desire for equilibrium; as a process through complementary; separation of responsibilities; purposeful regulation; the possibility of applying innovations and achievements of scientific and technological progress as an organization — is characterized by the properties of corporate identity, coordination of factors of production, rationality, ability to self-development. Co-operative and integration processes that can be represented as structural transformations of relations between the subjects of agrarian business at their joining into cooperative and integration interaction are studied. With a positive variant of interaction, the vector of the concept of "process" is the development, by which we understand the irreversible qualitative change of the subject or process associated with the complication or simplification of the production system, its adaptation to changing environmental conditions. It is established that the modern stage of development of cooperative and integration processes is characterized by convergence of principles of cooperation and integration in the conditions of development of social division of labor. However, together with the objective co-operation of the principles of cooperation and integration as a form of social division of labor, co-operation on the basis of mutual participation and integration on the basis of mutual complementary should be considered as a basic feature of co-operation.
Cooperation and integration in agrarian business
Keywords: кооперація; cooperative; кооператив; cooperative; інтеграція; integration; сільськогосподарський кооператив; agricultural cooperative; виробничий; production; споживчий; consumer; обслуговуючий; service; процес; process; система; system; структура; structure